2021
DOI: 10.18060/23805
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking study of hospital libraries

Abstract: Objectives: To assess the current landscape of hospital libraries by collecting benchmarking data from hospital librarians in the U.S. and other countries. Since the last MLA benchmarking survey in 2002 hospital libraries have faced significant changes including downsizing, position and library elimination, and hospital mergers. This survey will provides information to inform the development and implementation of effective advocacy for hospital libraries. Methods: A web-based, anonymous survey was designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Future benchmarking studies could dive deeper by collecting specific data that would correlating the number of staff support per individual library service. The 2019 study by Spencer, Mamo, and Billman published in February 2021 is a step in this direction [ 19 ].…”
Section: Detailed Standards Of Practice and Intentmentioning
confidence: 99%
“…Future benchmarking studies could dive deeper by collecting specific data that would correlating the number of staff support per individual library service. The 2019 study by Spencer, Mamo, and Billman published in February 2021 is a step in this direction [ 19 ].…”
Section: Detailed Standards Of Practice and Intentmentioning
confidence: 99%
“…Health and social services institution library closures and consolidations occur all too frequently, along with reduced staffing, space and budgets [42][43][44][45]. Practice that is not based on evidence risks causing harm to patients [46].…”
Section: Background Of the Standards Updatementioning
confidence: 99%
“…In both Canada [ 50 ] and the United States [ 51 ], recent assessment shows that hospital libraries are, for the most part, meeting but not surpassing the 2006 CHLA and 2007 MLA Standards respectively, so a complete overhaul was not deemed necessary [ 2 , 52 ]. In 2019, Spencer et al conducted a benchmarking study of hospital libraries and found that a large percentage of libraries did not have adequate staffing or budget and did not have a marketing and communications plan, or a strategic plan [ 44 ]. This confirmed the changes the Task Force proposed for the 2020 update, which emphasize the need for adequate staffing and budget, and highlighted the importance of strategic planning and assessment to show value and provide support for promotional endeavors (see Table 1 ).…”
Section: Background Of the Standards Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Benchmarking aims to enable libraries to compare their performance by gathering statistics from similar sites. The hospital libraries benchmarking study by Spencer, Mamo, and Billman (2019) obtained data from 180 North American respondents about services, client groups, funding, and activity. The libraries were predominantly small, with one or two staff, yet the majority offered a wide range of services, confirming the breadth of skills noted by McLaughlin et al (2018).…”
Section: Benchmark Surveysmentioning
confidence: 99%